1985
DOI: 10.1111/j.1439-0434.1985.tb00827.x
|View full text |Cite
|
Sign up to set email alerts
|

Physico‐Chemical Properties of Linseed Oil as Affected by Various Seed‐Borne Fungi

Abstract: The effect of six seed‐borne fungi on linseed oil was studied. Alternaria alternate, Aspergillus flavus, Aspergillus repens, Fusarium culmorum and Torula allii reduced oil content while Cladosporum herbarum slightly increased it. All fungi increased the free fatty acid content and saponification number linseed oil. Iodine number was decreased except in Cladosporium herbarum and Fusarium culmorum. Aspergillus flavus was the most destructive parasite in altering quantity and quality of linseed oil.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1999
1999
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 2 publications
(2 reference statements)
0
1
0
Order By: Relevance
“…In a study by Mondal and Nandi (1984) lipases of the fungi broke down the structure of the oil and the amount of free fatty acids increased as the oil content decreased as a consequence of treatment with fungi of the genus Aspergillus, decreasing its suitability for food and technical purposes. Dubey et al (1985) examined the effects of six typical storage fungi and found that four species, namely Aspergillus flavus, Aspergillus repens, Alternaria alternate and Torula allii, decreased the oil content of the seeds between 5% and 71% depending on the fungal species. Fusarium culmorum had no significant effect and Cladosporium herbarum increased the oil content.…”
Section: Effect Of Storage Chemical Composition and Microbiological mentioning
confidence: 99%
“…In a study by Mondal and Nandi (1984) lipases of the fungi broke down the structure of the oil and the amount of free fatty acids increased as the oil content decreased as a consequence of treatment with fungi of the genus Aspergillus, decreasing its suitability for food and technical purposes. Dubey et al (1985) examined the effects of six typical storage fungi and found that four species, namely Aspergillus flavus, Aspergillus repens, Alternaria alternate and Torula allii, decreased the oil content of the seeds between 5% and 71% depending on the fungal species. Fusarium culmorum had no significant effect and Cladosporium herbarum increased the oil content.…”
Section: Effect Of Storage Chemical Composition and Microbiological mentioning
confidence: 99%